PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI ELASTISITAS - Ludfianti, Eka; Sitompul, Stepanus Sahala; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to describe the implementation of the problem based learning model which could improve studentâ€™s learning outcomes on elasticity less onto class XI at SMA Negeri 6 Pontianak. The design of this study is a quasi-experimental (quasy experimental design) with Non Equivalent Control Group Design. The population used in this study was all of the students of SMA Negeri 6 Pontianak which consisted of four classes. The samples taken consisted of two classes. The sampling technique in this study was an intact group consisted of experimental group and control group with the total students of 34 students. The data collection tool in this study was the pre-test and post-test which consisted of 7questions. The results of the study using the two-sample t-test assuming unequal variances obtained p value of 1.40409 x 10-12 from the significance level of 0.05 (5%), which indicated that there were differences of improvement in studentâ€™s learning outcomes between students who used problem based learning model with students who used learning model that is often carried out by one of the physics teacher at the SMA Negeri 6 Pontianak.Keywords: Problem based learning model, Learning outcomes, ElasticityÂ